Visual and visuospatial development in young children with Williams syndrome. - Atkinson, J; Anker, S; Braddick, O; Nokes, L; Mason, A; Braddick, F (2001)
This study investigated the relation between sensory visual problems and the severity of visuospatial difficulties in a large group of young children with Williams' syndrome (WS). A questionnaire describing visual and associated problems was completed by the families of 108 children with WS and detailed follow-up assessments were conducted, including visual, spatial, motor, visuocognitive, and linguistic tests of 73 of these children (mean age 7 years 3 months; 40 males, 73 females). Children with WS showed a much higher incidence of common paediatric sensory vision problems (strabismus, visual acuity loss, amblyopia, reduced stereopsis) than normally developing children. It was found that delays with respect to age normative values increased with age on all tests. No significant correlation was found between the presence of a visual deficit and the severity of the visuospatial problems, suggesting that the difficulties children with WS have in understanding spatial arrangements are not simply a result of their earlier sensory visual problems. Results confirm the dissociation between visuospatial and language abilities in children with WS, and support the neurobiological model of a split between ventral and dorsal stream processing of visual information with a generalized deficit in dorsal stream processing in young children with WS.